RETRACTED: Features of the course of compensated, subcompensated and decompensated intestinal dysbiosis in cats - Tresnitskiy Sergey; Lutsay Vladimir; Ananev Lev; Sysoeva Natalya; Rudenko Andrei; Rudenko Pavel (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001